Dvarashakha of the garbhagriha of the Jain Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the entrance into the garbhagriha (sanctum sanctorum) of the Jain Temple is defined by a simple dvarashakha (door jamb) which has been renovated with bricks. The garbhagriha of the temple is currently empty. The original object of worship is not known and currently too the temple is not under worship.